HALAL MARKETING DYNAMICS: HOW CERTIFICATION, BRAND IMAGE, AND RELIGIOSITY INFLUENCE CONSUMER PURCHASE DECISIONS - Fitriana, Laily Annisa; Nabila, Rifda; Yudiana, Fetria Eka; Nabhan, Faqih; Waluyo, Agus; Rahman, Taufikur; Wibowo, Alip Tyas; Kanyi, Fatou (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The halal cosmetic industry has gained increasing attention as consumer demand for products that align with Islamic values continues to rise. This study aims to analyze the influence of halal certification, brand image, and religiosity on consumer purchase decisions, with a focus on Wardah cosmetic users in Salatiga, Indonesia. Primary data were collected through an online survey distributed via Google Form, with 384 respondents selected using purposive sampling and the Lemeshow formula at a 5% margin of error. Data were analyzed using SPSS 25 through multiple linear regression, supported by validity, reliability, normality, multicollinearity, and heteroscedasticity tests, as well as partial (t), simultaneous (F), and determination coefficient tests. The findings reveal that halal certification, brand image, and religiosity each have a positive and significant effect on purchase decisions. These results emphasize the importance of integrating halal assurance and brand positioning with consumers’ religious values to strengthen purchasing behavior in the halal cosmetic industry. This study contributes to the understanding of consumer behavior in the halal industry and offers strategic insights for policymakers and practitioners to enhance competitiveness and sustainability in both domestic and global halal markets.